During Hepatitis C Virus (HCV) Infection and HCV-HIV Coinfection, an Elevated Plasma Level of Autotaxin Is Associated With Lysophosphatidic Acid and Markers of Immune Activation That Normalize During Interferon-Free HCV Therapy. (17th August 2016) - Kostadinova, Lenche; Shive, Carey L.; Judge, Chelsey; Zebrowski, Elizabeth; Compan, Anita; Rife, Kelsey; Hirsch, Amy; Falck-Ytter, Yngve; Schlatzer, Daniela M.; Li, Xiaolin; Chance, Mark R.; Rodriguez, Benigno; et al.
Abstract: Background. Immune activation predicts morbidity during hepatitis C virus (HCV) infection and human immunodeficiency virus (HIV) infection, although mechanisms underlying immune activation are unclear. Plasma levels of autotaxin and its enzymatic product, lysophosphatidic acid (LPA), are elevated during HCV infection, and LPA activates immunocytes, but whether this contributes to immune activation is unknown. Methods. We evaluated plasma levels of autotaxin, interleukin 6 (IL-6), soluble CD14 (sCD14), soluble CD163 (sCD163), and Mac2 binding protein (Mac2BP) during HCV infection, HIV infection, and HCV-HIV coinfection, as well as in uninfected controls, before and after HIV antiretroviral therapy (ART) initiation and during interferon-free HCV therapy. Results. We observed greater plasma autotaxin levels in HCV-infected and HCV-HIV–coinfected participants, compared with uninfected participants, primarily those with a higher ratio of aspartate aminotransferase level to platelet count. Autotaxin levels correlated with IL-6, sCD14, sCD163, Mac2BP, and LPA levels in HCV-infected participants and with Mac2BP levels in HCV-HIV–coinfected participants, while in HIV-infected individuals, sCD14 levels correlated with Mac2BP levels. Autotaxin, LPA, and sCD14 levels normalized, while sCD163 and Mac2BP levels partially normalized within 6 months of starting interferon-free HCV therapy. sCD163 and IL-6 levels normalized within 6 months of starting ART for HIV infection. In vitro, LPA activated monocytes. Conclusions. These data indicate that elevated levels of autotaxin and soluble markers of immune activation during HCV infection are partially reversible within 6 months of initiating interferon-free HCV treatment and that autotaxin may be causally linked to immune activation during HCV infection and HCV-HIV coinfection.